Effect of tuna skin gelatin-based coating enriched with seaweed extracts on the quality of tuna fillets during storage at 4 °C - Milene Vala; Ana Augusto; Andre Horta; Susana Mendes; Maria M. Gil (International Journal of Food Studies)
Nowadays, consumers demand high quality food products with an extended shelf-life without chemical additives. Edible coatings (EC) containing natural compounds are a promising preservation technology for raw seafood without compromising fresh-like appeal and nutritional content. The aim of this work was to evaluate the effect of Thunnus obesus skin gelatin-based EC containing Codium spp. or Fucus vesiculosus extracts on raw tuna preservation. Three gelatin-based EC (gelatin (5 %) + glycerol (25 %); gelatin (5 %) + Codium spp. (1 %) + glycerol (25 %); gelatin (5 %) + Fucus vesiculosus (1 %) + glycerol (25 %)) were applied directly on the surface of tuna fillets. Functional properties of gelatin and gelatin-based EC containing seaweed extracts were also studied. The gelatin was extracted by an acid-swelling process in the presence/absence of pepsin, followed by subsequent heating/refrigeration, after a pre-treatment with NaOH. The type of acid, temperature and concentration of NaOH greatly influence the process yield. The higher extraction yield was achieved using acetic acid in the presence of pepsin by subsequent refrigeration, especially when skins were previously treated with NaOH (0.2 M). Tuna quality was assessed over 12 days of storage at 4 ± 1 °C in terms of chemical and microbial indices. Results showed that tuna skin gelatin-based EC avoids tuna deterioration. Microbial growth, assessed by total viable counts, and total volatile basic nitrogen were maintained below the maximum limits recommended, contrarily to the control. Additionally, the use of EC increased the stability of red colour during storage.